Formulación de los conceptos de riqueza y mantenimiento de riqueza (2012)
This work is going to development an inner definition about wealth and its conservation, taking into account economic, social and environmental elements, its main goal is to provide a better concept for the formulation of a general conceptual structure of the accountant models, which will be the beginning for the new accountant models in the construction field, the representation of the reality in different ways, not only the economic reality, finally contributing in the generation of reliable information would be a support in the well and correct decision-making. On the other hand, the accountant models, its main elements and characteristics have been structured over time according to the information needed by organizations and people, and taking into account the reality that is accountancy object of study. Nowadays, the financial accountant model is recognized and applied in more times than before, shifting economic content standards, pointing to realities of different conceptual and practical conditions as in social and environmental practices.